Agatha Christie and new directions in reading detective fiction narratology and detective criticism - Rolls, Alistair 1971- (Routledge, Taylor & Francis Group, 2022)
"This book brings a new lens to the work of Agatha Christie through a series of close readings which challenge the official solutions by Hercule Poirot and Miss Marple. This book's approach interweaves two core ideas: first, it explores the importance of French critic Pierre Bayard's self-styled 'detective criticism'; second, it takes detective criticism in a new direction by refocusing on the beginnings of Agatha Christie's novels. In this way, the book counters the end-orientation that has traditionally dominated the reading experience of, and critical response to, detective fiction by exploring the potential of the beginning to host other interpretations and stories. Offering a new way of reading detective fiction, this book is a mixture of narratology and detective criticism, and deploys it in the form of radical new readings of a number of Christie's most famous works. This illuminating text will interest students and scholars of crime and detective fiction, literary studies, and comparative literature"--
Keywords: Christie, Agatha -- 1890-1976; Kriminalliteratur; Christie, Agatha / 1890-1976 / Criticism and interpretation; Detective and mystery stories, English / History and criticism; English fiction / 20th century / History and criticism; Literary criticism